Národopis na Slovensku v službách tretej ríše - Panczová, Zuzana (Ethnological studies, 2021)
The publication is a contribution to the discussion of institutional and personnel tools of ideological use of ethnography and related scientific disciplines by Nazi Germany in the 1940s in the intentions of its foreign policy plans. It focuses on the efforts of the Third Reich and German researchers to influence the homeland and ethnographic research in Slovakia and follows it on the example of the activities of the Institute for homeland Research (Institut für Heimatforschung) in Kežmarok and those associated with its activities (Franz. J. Beranek and his wife Hertha Wolf-Beranek, Bruno Schier and others). The authors try to clarify the issues concerning the ideological contexts of ethnographic research of the German minority in Slovakia during the Second World War. They draw on period sources that have been preserved in the Institute of Ethnology and Social Anthropology of the Slovak Academy of Sciences and in other archival collections in Slovakia and abroad. The obtained archival data are also analysed with regard to the current research of the monitored issues in Slovakia, the Czech Republic, Germany and Poland. At the same time, the researched examples of the influence of Nazi ideology on the activity of specific personalities and institutions during the Second World War inspire a broader discussion on the relationship between political ideologies and science.